2006
DOI: 10.1016/j.gca.2005.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Predicting phosphate saturation in silicate magmas: An experimental study of the effects of melt composition and temperature

Abstract: A series of 1 atm experiments has been performed to test the influence of iron content and oxidation state on the saturation of phosphate minerals in magmatic systems. Four bulk compositions of different iron content have been studied. The experiments cover a range of temperature from 1030 to 1070°C and oxygen fugacity from 1.5 log units below to 1.5 log units above the Fayalite-Magnetite-Quartz buffer. The results demonstrate that neither iron content of the liquid nor oxidation state play a significant role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 45 publications
1
41
0
2
Order By: Relevance
“…apatite; Fig. 8; Tollari et al, 2006). These differences produced contrasted cumulate sequences in MCU I and MCU II and eventually affected magma chamber processes during crystallization.…”
Section: Effect Of Magma Mixing On Sept Iles Liquid Lines Of Descentmentioning
confidence: 94%
“…apatite; Fig. 8; Tollari et al, 2006). These differences produced contrasted cumulate sequences in MCU I and MCU II and eventually affected magma chamber processes during crystallization.…”
Section: Effect Of Magma Mixing On Sept Iles Liquid Lines Of Descentmentioning
confidence: 94%
“…3e). Experimental results indicate that the P 2 O 5 contents of magmas at apatite saturation vary negatively with SiO 2 and CaO and positively with temperature (Green and Watson, 1982;Tollari et al, 2006). Therefore, less P 2 O 5 is required for felsic magmas than mafic magmas at apatite saturation for a given temperature or at lower temperature for a given melt composition (Fig.…”
Section: Positive Eu Anomaly Of Apatite In the Mzb3mentioning
confidence: 99%
“…On the other hand, once Fe-Ti oxides or apatite are present on the liquidus, the other one will also crystallize in abundance (Tollari et al, 2006). Apatite is thus closely associated with Fe-Ti oxides in most cases.…”
Section: Enrichment Of Apatite In the Mzbmentioning
confidence: 99%
“…As previous investigations in terrestrial systems have indicated strong influence of silica activity [138][139][140] in the melt on the partitioning behaviour of OH between apatite and melt, it will be instructive to compare the results of these types of experimental studies with those carried out using the bulk composition of whole rocks. In addition, experiments should be conducted on a range of starting melt compositions with varying OH, F and Cl contents to crystallize apatites with a range in OH, F and Cl contents corresponding to compositional ranges observed in apatites from natural samples.…”
Section: (B) From the Perspective Of Mantle-derived Volcanic Productsmentioning
confidence: 99%